Kesepadanan Andung-Andung Batak Toba - Silalahi, Roswita; Purba, Parlindungan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
Andung-Andung (AA) ‘lamentation’ refers to expressions of sadness caused by the death of a loved one in the Toba Batak community. Lamentation consists of poetic expressions and is predominantly recited by grieving wives to express their deepest anguish, making it difficult to translate because of its unique linguistic and cultural features. This study was conducted to document and translate AA into Indonesian using a descriptive-qualitative method. The data were collected through observation, recording, interviews, content analysis, and focus group discussions (FGDs). The data were analyzed using an interactive analysis technique involving linguistic anthropology to interpret meaning, combined with content analysis and a meaning-based translation approach to produce an idiomatic translation.